2014
DOI: 10.1021/jp501881j
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Dual Fluorescence of Methyl Salicylate: Effects of Intermolecular Hydrogen Bonding and Solvation

Abstract: In this paper, we propose a new and complete mechanism for dual fluorescence of methyl salicylate (MS) under different conditions using a combined experimental (i.e., steady-state absorption and emission spectra and time-resolved fluorescence spectra) and theoretical (i.e., time-dependent density function theory) study. First, our theoretical study indicates that the barrier height for excited state intramolecular proton transfer (ESIPT) reaction of ketoB depends on the solvent polarity. In nonpolar solvents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(136 citation statements)
references
References 43 publications
11
125
0
Order By: Relevance
“…Letter Because the previous FDIRS study 24 showed no sign of II, there could be some reservations about the newly proposed mechanism 22 for the dual fluorescence of MS in protic solvents. If II does not exist in sufficient abundance, the ESIPT process cannot occur to produce sufficient intensity in the 440 nm band.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 97%
“…Letter Because the previous FDIRS study 24 showed no sign of II, there could be some reservations about the newly proposed mechanism 22 for the dual fluorescence of MS in protic solvents. If II does not exist in sufficient abundance, the ESIPT process cannot occur to produce sufficient intensity in the 440 nm band.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 97%
“…Although time‐dependent density functional theory (TDDFT) has become the most wide‐spread ab initio model to explore the electronically excited state properties of medium and large molecules due to its balance between computational efficiency and accuracy of results, using this model to deal with biradicals and conical intersections where double excitations play significant roles is difficult . TDDFT with certain conventional approximate functional typically underestimates the excitation energies of charge transfer (CT) states, and range‐separated (RS) functionals can be used as alternatives .…”
Section: Introductionmentioning
confidence: 99%
“…Using spectroscopic approaches, such as the electron absorption spectroscopic technique, fluorescence methods combined with the RLS technique, and mainly measurements of fluorescence lifetimes, we have shown the complexity of physical processes that exert an impact on the observed effects. The dual fluorescence effects can be induced in different molecules by changes in medium polarity, pH of the solution, temperature, or the concentration of the sample [2933]. According to theories attempting at elucidation of the observed fluorescence effects, they can be related to appearance of intramolecular CT states [34] and the so-called TICT states (Twisted Intramolecular Charge Transfer) [35, 36].…”
Section: Introductionmentioning
confidence: 99%